Cyclophosphamide and prednisolone for chemotherapy naïve B cell multicentric lymphoma in dogs: 32 cases (2017–2021). (14th October 2021) - Todd, J.; Thomas, P.; Nguyen, S.
Abstract : Objectives: The aim of this study was to characterise the response rate and toxicity profile of cyclophosphamide and prednisolone given to dogs with newly diagnosed, chemotherapy naïve, B cell multicentric lymphoma. Materials and Methods: Dogs with diagnosed with B cell lymphoma naïve to chemotherapy treatment were prospectively identified at the author's institution (2017 to 2021) and given cyclophosphamide as their initial chemotherapeutic agent in combination with prednisolone with owner's consent. Signalment, laboratory findings, stage, treatment response and toxicity were recorded. Results: Thirty‐two dogs were included in the study. The overall response rate in this population of dogs was 84%. Twenty dogs (62%) had a partial response, three dogs (9%) had a complete response, four dogs (12%) had stable disease and five dogs (15%) had progressive disease. Side effects were noted in 47% of patients, with neutropaenia being the most commonly reported. Clinical Significance: Cyclophosphamide and prednisolone were well‐tolerated with limited side effects. The response rate observed in this cohort of dogs with chemotherapy‐naïve B cell multicentric lymphoma is promising. Further comparative studies are required to confirm the safety and effectiveness of this intervention.